Perlukah Menunda Perawatan Ortodontik Sampai Periode Geligi Tetap? - Nia Ayu Ismaniati (Faculty of Dentistry, Universitas Indonesia, 2015)
Individuals with skeletal discrepancy often come when growing is no longer expectable. This may occur due to the "myth" saying that the best timing for orthodontic treatment is to wait until all permanent teeth eruption (except the wisdom teeth) or to wait until the age of 12. With better nutrition, perhaps, nowadays, adolescents mature much earlier. Sometimes, 2-3 years before the age of 12, all deciduous dentition has been exfoliated. Thus, when orthodontic treatment started at this age, not much growth modification can be applied since not much growth can be expected. This often leads to a more difficult and complex orthodontic treatment. It is wise to pay attention early and treat it if necessary, when discrepancy is detected, due to prevent further facial and dental deformity. Skills in establishing a proper diagnosis and treatment plan and determining the time when to start an orthodontic treatment are essential. It is also necessary to recognize the puberty signs in regards to apply the optimal growth potential for growing patients. Timing the individual permanent teeth eruption, the completion of root formation also factors to be thoroughly considered when treatment needs to be commenced in the mixed dentition stage.